Doctors save lives; psychologists save existences: mental health 5G? The role of research and teaching in the current university paradigm - Luísa Soares (Universidade Estadual de Alagoas, 2024)
Scientific events are important for maturing and debate about science and as such, it is suggested a reflection on a paradigm shift that seems to be taking place, which is mental health is also health vs the previous paradigm called mental health is health. This change occurs, particularly in this post-pandemic context. We are already in the mental health is health paradigm, without which everything else ceases to make sense, or even to exist. Hence the title of this reflective paper: Doctors save lives; psychologists save existences: mental health 5g? Reflecting on the urgency and speed (such as 5G internet) to implement behavioral changes in mental health, this work was presented as a keynote speaker at the 14th National Congress of Health Psychology (which occurred on 8th-10 th of September 2022). It is hoped to reflect and raise some questions rather than answer them.